Weseretkau "Mighty of kas" : papers in memory of Cathleen A. Keller - Kiser-Go, Deanna; Redmount, Carol Ann, 1952-; Keller, Cathleen A. (Lockwood Press, 2023)
"Weseretkau "Mighty of Kas" honors the life and career of Professor Cathleen "Candy" Keller, a truly extraordinary teacher, scholar, Egyptologist, and polymath. The contributors to this volume were Professor Keller's students, friends, and colleagues. Though much of the research presented here centers around the honoree's two primary passions-Egyptian art and the study of the village of Deir el-Medina-the range of topics reflects her broad Egyptological interests, including religious organization, artistic technique, museum collections, textual analyses, historical events, and archaeological studies at sites throughout Egypt"--